Responses of tonically active neurons in the primate's striatum undergo systematic changes during behavioral sensorimotor conditioning - Aosaki, T (J Neurosci, 1994)
The basal ganglia have been implicated in motor planning and motor learning. In the study reported here, we directly tested for response plasticity in striatal neurons of macaque monkeys undergoing Pavlovian conditioning. To focus the study, we recorded from the tonically active neurons (TANs) of the striatum, which are known to respond to conditioned sensory stimuli that signal reward delivery and elicit behavioral reactions. The activities of 858 TANs were recorded extracellularly from the striatum in alert behaving macaque monkeys before, during, and after the acquisition of a classical conditioning task. Two monkeys were trained to lick reward juice delivered on a spoon simultaneously with the presentation of a click. Almost no licks were triggered by the cues at the start of training, but by the fifth day more than 90% of licks were triggered, and values were near 100% for the remainder of the 3 week training period. In the striatum, only a small number of TANs responded to the clicks at the start before conditioning (about 17%). During training, the numbers of responding TANs gradually increased, so that by the end of training more than 50– 70% of the TANs recorded (51.3–73.5%) became responsive to the clicks. The responses consisted of a pause in firing that occurred approximately 90 msec after the click and that was in some cells preceded by a brief activation and in most cells was followed by a rebound excitation. Prolonged recordings from single TANs (n = 6) showed that individual TANs can acquire a conditioned response within at least as short a time as 10 min. TANs retained such responsiveness after overtraining, and also after a 4 week intermission in training. When the monkey was trained to receive rewards in relation to a new conditioning stimulus, TANs were capable of switching their sensory response to the new stimulus. Histological reconstruction showed that the TANs that became responsive were broadly distributed in the region of striatum explored, which included the dorsal half to two-thirds of the caudate nucleus and putamen over a large anteroposterior span. We conclude that, during the acquisition of a sensorimotor association, TANs widely distributed through the striatum become responsive to sensory stimuli that induce conditioned behavior. This distributed change in activity could serve to modulate the activity of surrounding projection neurons in the striatum engaged in mediating learned behavior.